ANALISIS PERILAKU GENERASI MILENIAL TERHADAP PRODUK SKINCARE THE ORIGINOTE - Dwi Putri, Adinda Azmi; Firmathoina, Aisyah; Sya’ban, Muhammad Adib; Nofirda, Fitri Ayu (Creative Research Management Journal, 2023)
This research was carried out with the aim of finding the influence of e-commerce, trust and brand image on purchasing decisions. The research procedure involved the application of linear regression analysis, t test, f test, and calculation of determinant coefficients on a sample of 50 students at Muhammadiyah University of Riau. Data collection was carried out using a questionnaire. The findings from the research show that there is a negative impact of e-commerce and trust on purchasing decisions and conversely, brand image has a positive influence on purchasing decisions. The t and f tests show that the influence of e-wom, brand trust and brand image on purchasing decisions is significant. In addition, brand image has been shown to have a considerable positive impact on purchasing decisions, with brand standing out as the most influential factor. The limitation of this research lies in the use of data that includes respondents' views on the statements submitted in the research questionnaire, some respondents filled out the questionnaire without taking each statement seriously. However, it is hoped that the indicators presented in this research can serve as guidelines for sellers of The Originote skincare products in Pekanbaru.